KEBENARAN AL QUR'AN DAN HADITS DARI SUDUT PANDANG FISIKA SAINS - Agus Azhar Harahap (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
This journal discusses about the scientific that is often a debate of scientists. Some scholars argue that the Qur'an motivates its people to love science. Other experts argued that the verses of the Qur'an gives signals of science, but in fact these thoughts comes down to the same goal which confirmed the contents of the content of the Koran and Hadith through scientific research conducted by scientists Muslim or non-Muslim. In the latest developments strengthen the stretch of Muslims about the necessity of Islamization of science. Approach in this journal is a science approach that explores the truth content of Al Qur'an and Hadith content through scientific research. In this context, Islam not only encourages its people to love science, but it gives a scientific signal which if revealed will result in the work of science that contributes to human civilization, so that the presence of science provides convenience in the survival of the creatures of the world. The authors conclude that the existence of science gained significant support in the teachings of Islam to be an integral part of the system of Islamic theology.